Role of Ophthalmic Nurses in Prevention of Ophthalmic Diseases - Hadavand, Mohammad Bagher (Medical Hypothesis, Discovery & Innovation Ophthalmology, 2013)
There are numerous ocular problems that could be diagnosed and detected by well-trained ophthalmic nurses. Ophthalmic nurses may significantly contribute in ophthalmology and visual sciences. These trained nurses may assist in decrease the rate of cancelled surgical operations at the date of operation that had been due to lack of attention to health problems in pre-operative assessments. Furthermore, they could perform some medical evaluation of patients that are candidates for surgery, preoperatively. Additionally, their services would be beneficial to accelerate discharging patients, which would result in less drain on financial resources for medical centres. Ophthalmic nurses are also critical elements in health-care systems because they can help to deliver up to date ophthalmic knowledge and contribute to general physicians, academically. Additionally, they may be able to assist patients who suffer from blindness or loss of vision, to find national organizations that provide services and education. They are able to be a great assistance in referring patients that need subspecialty services and subsequently, contribute to saving health-care expenditures by let the patients to receive proper management. These nurses could play a significant role in the process of teaching people, providing proper diagnoses, administration, and management of ocular problems.